Intervenção para urbanização de assentamentos precários no bairro João Pessoa-PB: uma abordagem da regularização fundiária de assentamentos urbanos irregulares em áreas de preservação permanente. - Dunda, Bruno Faro Eloy (2014)
Most Brazilian cities, either big or medium seized, live together with informal and precarious human settlements which are located in environmentally sensitive and legally protected areas and whose solution represents one of the greatest challenges of public managers. It is estimated that more than twelve million urban homes in Brazil which are occupied by low income people are irregular. This is a real fact to be faced by the public administration, always taking into consideration that there was not a legal alternative of dwelling to the families who live illegally in the settlements. The need to regularize these informal settlements located in environmentally protected areas and, therefore, with restricted occupation to exceptional cases, places ordinary legislators and public administrators between two constitutionally sacred values: the social right to housing and the right to a balanced environment. The Legislative or administrative option for one of these two constitutional values, does not provide a satisfactory solution to face the problem of the informal and precarious settlements. By choosing only the regularization of the land ownership and ensuring legal security for residents of the informal settlements located in environmentally sensitive areas, the legislator and the public administrator would ignore people¿s diffuse right to an ecologically balanced environment which is essential to the healthy life for actual and future generations. On the other hand, a strict application of the environmental standards by vacating the area and its subsequent rebuilding would respect the obligation of preserving the environment, but would also empty the contents of the social right to housing. In this context, the regularization of settlements in permanent preservation areas, as conceived by the Brazilian law, represents the achievement of technical proportionality or the balance, in the face of the collision of two constitutionally sacred values and not as an environmental backlash. This ensures, at the same time, the consecration and the compatibility of the constitutional values which are considered here, namely, the social right to housing and the right to an ecologically balanced environment.